Beyond the Channels: Adhesion Functions of Aquaporin 0 and Connexin 50 in Lens Development - Li, Zhen; Quan, Yumeng; Gu, Sumin; Jiang, Jean X. (Frontiers in Cell and Developmental Biology, 2022)
Lens, an avascular tissue involved in light transmission, generates an internal microcirculatory system to promote ion and fluid circulation, thus providing nutrients to internal lens cells and excreting the waste. This unique system makes up for the lack of vasculature and distinctively maintains lens homeostasis and lens fiber cell survival through channels of connexins and other transporters. Aquaporins (AQP) and connexins (Cx) comprise the majority of channels in the lens microcirculation system and are, thus, essential for lens development and transparency. Mutations of AQPs and Cxs result in abnormal channel function and cataract formation. Interestingly, in the last decade or so, increasing evidence has emerged suggesting that in addition to their well-established channel functions, AQP0 and Cx50 play pivotal roles through channel-independent actions in lens development and transparency. Specifically, AQP0 and Cx50 have been shown to have a unique cell adhesion function that mediates lens development and transparency. Precise regulation of cell-matrix and cell-cell adhesion is necessary for cell migration, a critical process during lens development. This review will provide recent advances in basic research of cell adhesion mediated by AQP0 and Cx50.